PENGARUH PROFESIONALISME DAN KEPUASAN KERJA TERHADAP KUALITAS AUDITI - Ni Luh Putu Sukesiyanti; Ni Wayan Alit Erlina Wati (UNHI Press, 2020)
This study aims to determine the effect of auditory professionalism and job satisfaction in the face of auditee quality at the Public Accountant Office in Bali Province. The agency theory related to the auditee problem shows that the request for auditee services arises because there is a conflict of interest between management as an agent and an owner understands as a principal. This research was conducted at the Public Accountant Office in Bali with eleven offices in 2019 with 99 auditory people as samples through the purposive sampling method. Data collection is done by distributing questionnaires. 45 questionnaires were analyzed through moderation analysis regression (MRA) technique. The results showed that professionalism had a positive effect on auditee quality with a parametric coefficient value of 0.798 with a significance level of 0.000. This means that there is a high level of professionalism so that the quality of the auditee will be higher and will be found to produce highly qualified auditee reports. Job satisfaction does not affect the auditee quality with a parametric coefficient value of 0.183 with a significance level of 0.117. This means that in order to fulfill the maximum performance of an auditory person, it must be based on the seriousness of the time which is measured by the quality of the work produced.